2012
DOI: 10.1038/bjc.2012.393
|View full text |Cite
|
Sign up to set email alerts
|

Overestimation of carboplatin doses is avoided by radionuclide GFR measurement

Abstract: Background:Glomerular filtration rate (GFR) is used in the calculation of carboplatin dose. Glomerular filtration rate is measured using a radioisotope method (radionuclide GFR (rGFR)), however, estimation equations are available (estimated GFR (eGFR)). Our aim was to assess the accuracy of three eGFR equations and the subsequent carboplatin dose in an oncology population.Patients and methods:Patients referred for an rGFR over a 3-year period were selected; eGFR was calculated using the Modification of Diet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
1
21
1
3
Order By: Relevance
“…Craig et al found all estimating equations (MDRD, CKD-EPI, CG) to be associated with carboplatin overdosing (in 60-80% of cases) in a wide spectrum of oncology patients with the majority of subjects having gynaecological, lung, lymphoma and upper GI cancers (24). This study highlights the difficulties in using estimating equations to calculate carboplatin doses in oncology patients.…”
Section: Effect Of Estimating Gfr On Carboplatin Prescribingmentioning
confidence: 82%
“…Craig et al found all estimating equations (MDRD, CKD-EPI, CG) to be associated with carboplatin overdosing (in 60-80% of cases) in a wide spectrum of oncology patients with the majority of subjects having gynaecological, lung, lymphoma and upper GI cancers (24). This study highlights the difficulties in using estimating equations to calculate carboplatin doses in oncology patients.…”
Section: Effect Of Estimating Gfr On Carboplatin Prescribingmentioning
confidence: 82%
“…Although useful for identifying patients with renal impairment, it is too inaccurate across the full range of GFR for purposes such as determining chemotherapy dosing (1)(2)(3). More recently, the Modification of Diet in Renal Disease (MDRD) (4) and the CKD-EPI (Chronic Kidney Disease Epidemiology Collaboration) (5) formulae have been shown to provide more accurate estimations.…”
mentioning
confidence: 99%
“…Toutes ces é tudes sont cependant des simulations et nous en ré sumons les principales dans le Tableau 2 [49,50,52,[54][55][56][57][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84]. À la vue de ce tableau, le moins que l'on puisse dire est que les é tudes ne sont pas toujours d'une qualité mé thodologique irré prochable (notamment en termes de « cré atinine »), que les mé thodologies et les simulations sont parfois assez diffé rentes, et enfin que les ré sultats de ces publications, en termes du choix de la formule, sont trè s contradictoires.…”
Section: Le Choix De La Formule : Que Nous Dit La Litte´rature ?unclassified
“…C'est le cas, par exemple, dans le contexte d'une chimiothé rapie né phrotoxique, qui plus est si la fenêtre thé rapeutique est é troite et/ou si le patient concerné a un gabarit hors norme. Ainsi, avant une chimiothé rapie à base de dé rivé s du platine, certains auteurs recommandent une mesure du DFG afin d'adapter au mieux la dose à administrer (formule de Calvert et d'Eckardt) [66,79,81,82,108]. La place du DFGm dans la problé matique de l'adaptation posologique est en fait centrale et devrait être considé ré e dè s les premiè res phases de dé veloppement des mé dicaments.…”
Section: L'inté Rêt Primordial Du Dfgmunclassified